Results of Monitoring Eastern Imperial Eagle Breeding Populations in Dagestan (Russia) in 2022–2023 - Gadzhibek S. Dzhamirzoev; Rinur H. Bekmansurov; Hadzhaman N. Ismailov (Пернатые хищники и их охрана)
Eastern Imperial Eagle (EIE; Aquila heliaca) breeding populations in Dagestan were monitored in 2021 and 2022 as part of the project “Study and Conservation of Eastern Imperial Eagle” implemented by the Non-governmental Environmental Central “Caucasus”, Russian Bird Conservation Union (RBCU), and Nature and Biodiversity Conservation Union NABU, with the support of the NABU International Foundation and VGP Foundation.